Pengaruh Kompetensi dan Disiplin Kerja Terhadap Kinerja Pegawai Biro Sumber Daya Manusia Aparatur dan Organisasi Kementerian Kelautan dan Perikanan Republik Indonesia - Ade Nanda Saputri; Ratnawaty Marginingsih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The Bureau of Apparatus Human Resources and Organization is one of the echelon II work units at the Secretariat General of the Ministry of Maritime Affairs and Fisheries of the Republic of Indonesia which has the task of coordinating, fostering and managing the human resources of the apparatus within the Ministry of Maritime Affairs and Fisheries. The Bureau of Human Resources Apparatus and Organization in managing human resources needs to pay anttention to the competence and work discipline of each employee in order to produce quality employees and superior performance. This study aims to determine the effect of competence and work discipline on employee performance of the Bureau of Human Resources Apparatus and Organization of the Ministry of Maritime Affairs and Fisheries of the Republic of Indonesia. The research method used is quantitative method with data collection using saturated samples or non probability sampling. A total of 64 respondents were sampled and the data obtained was processed using SPSS 25 software with multiple linear regression analysis techniques which included instrument testing, partial and simultaneous hypothesis testing. The results showed that there was a positive and significant influence, partially and simultaneously competence and work discipline on the performance of employees of the Bureau of Human Resources Apparatus and Organization of the Ministry of Maritime Affairs and Fisheries of the Republic of Indonesia.